Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1152/ajpregu.2001.281.2.r607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of catecholamines on the pulmonary circulation in the ovine fetus

Abstract: High levels of circulating catecholamines are found in the fetus, and fetal stress and birth induce a marked surge in catecholamine secretion. Little is known about the role of catecholamines on the fetal pulmonary circulation. To determine the effects of catecholamines on the pulmonary vascular tone, we tested the hemodynamic response to norepinephrine and dopamine infusion in chronically prepared late-gestation fetal lambs. We found that norepinephrine infusion (0.5 microg. kg(-1). min(-1)) increased pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
29
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 40 publications
2
29
0
4
Order By: Relevance
“…Finally, in our study, basal PVRs were in the same range as those measured in previous studies (17,32,33).…”
supporting
confidence: 87%
See 3 more Smart Citations
“…Finally, in our study, basal PVRs were in the same range as those measured in previous studies (17,32,33).…”
supporting
confidence: 87%
“…In vitro studies have reported that relaxant effects of norepinephrine observed in some systemic (15) and pulmonary (16) vessels in newborn animals result from endothelial ␣ 2 -adrenoceptor activation. Our in vivo studies further support the hypothesis that norepinephrine may activate ␣ 2 -adrenoceptors: 1) norepinephrine induces a potent pulmonary vasodilation in fetal lambs (17); 2) norepinephrineinduced pulmonary vasodilation is mediated by NO production (17); 3) selective ␣ 2 -adrenoceptor blockade abolishes the pulmonary vasodilator response to norepinephrine; and 4) the ␣ 2 -agonist UK 14,304 mimics the effects of norepinephrine on the pulmonary circulation. High circulating norepinephrine levels are found during fetal life (10,11).…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Stress hormones have also been shown to modulate the pulmonary vascular tone and reactivity during the perinatal life (12,26,29). These data suggest that perinatal stress may alter the pulmonary circulation.…”
mentioning
confidence: 91%